Severe Congenital Protein C Deficiency: Practical Aspects of Management. Issue 8 (2nd May 2016) - Shah, Ravi; Ferreira, Patrick; Karmali, Shelina; Le, Doan
Abstract : Subcutaneous (SC) protein C (PC) was used in a child with purpura fulminans secondary to severe congenital PC deficiency. For maintenance, PC 80–120 IU/kg, given over 60–90 min SC Q48hr, has been successful as a home therapy for more than 3 years. The treatment was monitored by measuring trough PC chromogenic activity (target ≥15%) and D‐dimer levels. No change in clinical course was appreciated after discontinuing enoxaparin (and leaving the patient on prophylactic PC replacement alone). A significant discrepancy between clotting‐based and chromogenic‐based PC activity is shown.